The relationship between MTHFR gene polymorphisms,plasma homocysteine levels and diabetic retinopathy in type 2 diabetes mellitus - 孙家忠 徐焱成 朱宜莲 鲁红云 邓浩华 范幼筠 孙苏欣 张颖 (Chinese medical journal, 2003)
Objective To evaluate the role of methylenetetrahydrofolate reductase(MTHFR)gene polymorphisms and plasma homocysteine levels in patients with type 2 diabetes mellitus and diabetic retinopathy(DR).Methods Total of 208 patients with type 2 diabetes mellitus and 57 controls were recruited into the study.MTHFR genetic C677T polymorphisms were determined by PCR-RFLP.Plasma total homocysteine levels were measured using high-performance liquid chromatography(HPLC)with fluorescence detection.Results The frequencies of MTHFR TT homogeneous type,CT heterogeneous type and allele T (28.18?41.82?49.09?were significantly higher in the type 2 diabetes mellitus with diabetic retinopathy group than those without retinopathy(18.37?29.59?33.16?and those of controls (17.54?28.07?31.58?.The presence of the T allele appeared to have a strong association with the development of diabetic retinopathy.The odds ration was 1.94 with a 95?confidence interval of 1.31-2.88.Moreover,plasma homocysteine levels were remarkably higher in patients with TT or CT genotype than in patients with the CC genotype.Concluslon MTHFR gene C677T mutation associated with a predisposition to increased plasma homocysteine levels may be considered as a genetic risk factor for diabetic microangiopathy(such as DR)in Chinese patients with type 2 diabetes mellitus.